2015
DOI: 10.1089/lgbt.2014.0092
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Negative Partnered Men's Willingness to Use Pre-Exposure Prophylaxis and Associated Factors Among an Internet Sample of U.S. HIV-Negative and HIV-Discordant Male Couples

Abstract: Purpose: Research on male couples' willingness to use pre-exposure prophylaxis (PrEP) is critically lacking. Methods: A cross-sectional 2011 Internet survey collected dyadic data from 275 HIV-negative and 58 HIVdiscordant male couples to describe 631 HIV-negative partnered mens' willingness to use PrEP and associated couple-level demographic and behavioral factors with multivariate multilevel modeling. Results: Fifty-three percent were very to extremely likely to use PrEP. Willingness was positively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…Recent Canadian studies reported willingness to use PrEP of 55.0% [62,63]. In the US where the majority of studies on PrEP have been conducted, willingness to use PrEP has ranged from 46.1% to 71.0% [64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Recent Canadian studies reported willingness to use PrEP of 55.0% [62,63]. In the US where the majority of studies on PrEP have been conducted, willingness to use PrEP has ranged from 46.1% to 71.0% [64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Other characteristics about this sample have been reported, including their use of risk-reduction strategies, HIV and STI testing behaviors, aspects about their sexual agreements, and attitudes toward using pre-exposure prophylaxis and couples-based HIV testing and counseling [8, 9, 43, 44, 45]. …”
Section: Methodsmentioning
confidence: 99%
“…Board approved the study protocol; methods have been previously described. 7,23,26,27,30 Recruitment for this study sample was conducted through Facebook banner advertising in 2011. Advertisements targeted partnered men who reported in their Facebook profile being ‡18 years of age, living in the U.S., interested in men, and being in a relationship, engaged, or married.…”
Section: The Medical College Of Wisconsin Institutional Reviewmentioning
confidence: 99%
“…Though studies have reported that most single and partnered MSM are willing to use PrEP, [5][6][7][8] less attention has been given to assessing their willingness to use nPEP. Non-occupational PEP is a 28-day course of 3 antiretroviral medications, that should be taken within 72 hours after a potential exposure to HIV.…”
Section: Introductionmentioning
confidence: 99%